Electro-optical displays - Karim, Mohammad A. (Optical engineering (Marcel Dekker, Inc.), 1992)
This comprehensive reference covers the principles, applications, and issues pertaining to all major electro-optical displays presently in use -- discussing display evaluation characteristics and human factor topics that impact on the performance of display systems.